The Effect of Listening Task Complexity and Offline Learning on Postural Control - Raziyeh Sajedi; Parvaneh Shamsipour Dehkordi; Leila Ghazaleh (Ṭibb-i Tavānbakhshī, 2022)
Background and Aims Postural control of the kinetic variable of motion plays an essential role in maintaining stability in daily activities. Dual tasks for studying balance or postural control are accompanied by cognitive tasks. The aim of the present study was to investigate the effect of listening task complexity and offline learning on postural control.Methods Twenty-eight employees with an age range of 30-40 years from Alzahra University of Tehran (PBUH) were selected by available sampling and based on inclusion criteria and divided into three groups with different training distributions of 2 minutes, 15 minutes, and 24 hours with three levels of difficulty (easy, medium, and difficult). Each group performed three blocks of six attempts with each attempt time of 35 seconds, the interval between attempts of 20 seconds, and the time interval between blocks depending on the division of the group: 2 minutes, 15 minutes, and 24 hours with three difficulty levels. Findings were analyzed using a combined factor analysis of variance with repeated measures of three groups (mass, 15 minutes, and 24 hours) and three task levels (easy, moderate, and difficult) and the Bonferroni post hoc test.Results Findings showed that the main effect of homework difficulty level and practice distribution was significant (P=0.001) and in the retention stage, there was a significant difference between the mean frequency power in the anterior-posterior direction in the low difficulty listening group and the high difficulty listening group. In the listening task, the interactive effect of task difficulty level in the distribution of practice was not significant. In the memorization stage, regarding the COP components (average frequency power in the anterior-posterior direction), the training group (24 hours), and in the listening task with an easy complexity level, the best condition was posture control, and in the training group (2 minutes) and in the listening task with difficult complexity level, the weakest condition was control posture. In the listening task with a high level of difficulty, the 24 hour training group had better average COP components than the mass training group and the 15 minute training group.Conclusion It seems that distance training over mass training along with the parameters of strengthening motor memory increases cognitive effort and motivation. According to Hacken, Kelso, and Bondes hypothesis (progress-regression), educators should include homework in teaching instruction and from simple to difficult in the curriculum.